Optimizing High-Speed Train Timetabling with Consideration of Sta-tion Carrying Capacity - Chunxiao Chen; Wenjing Li (Decision Making: Applications in Management and Engineering, 2025)
The extensive development of high-speed railways (HSR) in China has transformed the railway system from one constrained by limited capacity to a more adaptable network, significantly mitigating previous capacity shortages. Nevertheless, the demand for high-speed rail services exhibits considerable variability, with peak travel periods—such as the Spring Festival, summer holidays, and extended weekends—increasingly becoming regular occurrences. During these peak times, passenger flows become highly concentrated, resulting in temporary congestion at certain high-traffic HSR stations. Current methodologies for assessing the carrying capacity of HSR stations predominantly rely on approaches originally designed for conventional railways. These methods often fail to adequately consider the unique characteristics of individual stations, their equipment, and operational specifics. The parameters employed are frequently broad and lack precision, underscoring the necessity for more refined techniques to calculate station capacity and develop accurate HSR timetables that can better accommodate peak travel demands. This research initially integrates the train dispatching principles of HSR station CTC (Centralised Traffic Control) systems with automatic point sampling principles to conduct a comprehensive analysis of critical parameters. These parameters include train occupancy durations on arrival and departure tracks, train occupancy times in throat areas, and daily idle periods. The values of these parameters are refined and standardised to ensure that the outcomes of the comprehensive analysis method align more closely with actual operational requirements. Subsequently, with the objective of minimising total travel time, this study formulates a single-objective mathematical programming model for generating HSR timetables that incorporate station carrying capacity constraints. A genetic algorithm is also developed to solve this model. Utilising operational data from the Shanghai-Hangzhou East HSR, the study constructs a timetable under the constraints of station capacity, assesses the influence of both the timetable and the algorithm on the results, and verifies the efficacy of the proposed model and algorithm.